Dandy-Walker Syndrome – review of patients’ health situation in Poland - Guz, Ewa Teresa; Turowski, Krzysztof; Czekirda, Marta; Bartoń, Elżbieta (Journal of Education, Health and Sport, 2016)
Guz Ewa, Turowski Krzysztof, Czekirda Marta, Bartoń Elżbieta. Dandy-Walker Syndrome – review of patients’ health situation in Poland. Journal of Education, Health and Sport. 2016;6(8):181-189. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60072 http://ojs.ukw.edu.pl/index.php/johs/article/view/3742 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 12.08.2016. Dandy-Walker Syndrome – review of patients’ health situation in Poland Ewa Guz, Krzysztof Turowski, Marta Czekirda, Elżbieta Bartoń 1. Ewa Guz Neurology Nursing Department, Medical University in Lublin 8 Jaczewskiego Street; 20-950 Lublin 2. Krzysztof Turowski Director of Neurology Nursing Department, Medical University in Lublin 8 Jaczewskiego Street; 20-950 Lublin 3. Marta Czekirda Faculty of Nursing and Health Sciences, Medical University of Lublin Department of Pedagogy and Medical Didactics 1 Racławickie Av. 20-059 Lublin 4. Elżbieta Bartoń Neurosurgery and Pediatric Neurosurgery Clinic in Lublin 8 Jaczewskiego Street; 20-950 Lublin Key words: Dandy-Walker syndrome, dysplasia, hydrocephalus, intraventricular shunt. Abstract Dandy-Walker syndrome is a congenital defect of a central nervous system characterized by a hindered flow of cerebrospinal fluid through the outflow holes of ventricle IV. Symptoms of the disease can develop slowly since the early childhood and will result in developing both hydrocephalus and anomalies related to the structure of the cerebellum. The etiology of Dandy-Walker syndrome is not known. Aim of this work is to present the health situation of the patients with Dandy-Walker syndrome in Poland. Material and methods The research was conduncted from December 2011 to April 2012 and involved the group of wards of the ‘Podaj Dalej’ Dandy-Walker Syndrome Foundation who live on the territory of Poland. Overall, 36 people were examined: 15 boys and 21 girls. Results and conclusions Reaching the patients with Dandy-Walker syndrome is very difficult because it is a rarely occurring congenital defect, recognized usually by accident. However, the complexity of problems evolving from this disease brings the necessity of expanding the studies in many areas so they could be compared to the studies conducted in other countries. Results of this type of studies will be useful in a correct orientation of treatment and widely understood rehabilitation of patients with Dandy-Walker syndrome as well as education both families and the patients.